Адвокаттық қызмет тəжірибесін реттеудің кейбір мəселелері (ТМД елдерінің заңнамаларының салыстырмалы-құқықтық анализі: Армения, Əзірбайжан, Қазақстан, Қырғызстан, Тəжікстан жəне Өзбекстан елдері материалынан) - Nurmaganbet, E.T. (Journal of actual problems of jurisprudence, 2019)
In given article the rather-legal analysis of acts of some the CIS countries regulating activity of legal profession, its development, cooperation in this sphere was considered. In the present article the attention only to some aspects of realization of the lawyer practice interesting, in our opinion, which regulation in each republic has original, distinctive character is paid.